The Correlation between Mathematics and Physics Achievement of Senior High School Students - Chen Jihe; Jerito Pereira; Xinxin Li; Ying Zhou; Maximus Tamur; Syaharuddin Syaharuddin (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2021)
Physics and mathematics are the two most closely related natural rudimentary subjects. In physics, students often need to rely on rigorous mathematical reasoning and argumentation and use various mathematical methods for investigation, reasoning, calculus, test, and discussion, but students often appear in these difficulties. This research aims to explain the influence of mathematics achievement on physics achievement from the high school mathematics achievement and physics achievement. The results of math and physics in the first semester of 6 classes of senior high school student's grade 12 were selected, and the data were analyzed with SPSS.22 software, and three students of different learning abilities were interviewed in detail. The innovation of this paper lies in the use of hierarchical research methods to compare classes of mathematics achievement and physics achievement. The conclusions are (1) in objective level, there is a positive linear relationship between math achievement and physics achievement; (2) on the subjective level, students accept the view that the performance of mathematics can promote the performance of physics; students' subjective cognition will affect their cognitive structure and learning behavior, to actively seek for the relationship between mathematical knowledge and physical knowledge, and then slowly affect the objective level of students, and then in mathematics and physics performance, and (3) applying mathematical thinking to physics learning can improve the efficiency of learning physics. Use mathematical knowledge of trigonometry to solve the force analysis problem of physical movement. The finding shows that math scores play a significant role in physics scores. Remind us that in teaching, we should pay attention to the integration of mathematical ideas into physics learning and help students learn physics knowledge better with mathematical ideas.